PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS PROSEDUR BERBANTUAN APLIKASI CANVA - Nur Lenasari; Wikanengsih; Iis Siti Salamah Azzahra (IKIP Siliwangi, 2026)
This study aims to improve the procedural text writing skills of seventh-grade students through the application of the discovery learning model assisted by the Canva application. The background of this research lies in the students’ low writing skills, which are caused by a lack of interest in writing, the use of conventional teaching methods, and unappealing learning media. The purpose of this study is to examine the implementation of the discovery learning model using the Canva application in writing instruction.This research adopts a mixed-method approach with an exploratory sequential design. The subjects of the study were 20 seventh-grade students of MTsS Muslimin Cicangkanggirang. Data collection techniques included observation, interviews, questionnaires, and tests. The findings indicate a significant improvement in students’ procedural text writing skills after the application of the discovery learning model assisted by Canva. The average post-test scores of the students increased significantly compared to their pre-test scores. This demonstrates that the discovery learning model, when integrated with Canva, can foster more active, creative, and motivated student participation in procedural text writing. These findings contribute to the innovation of Indonesian language learning, particularly in the area of writing skills. Therefore, the application of this model is highly recommended for teachers in teaching procedural text writing at the junior high school level.